Originally Posted by

**pflo** Couldn't you look at it this way:

.$\displaystyle x^2 - 2x + 1 \:\le \:0 \quad\Rightarrow\quad (x-1)^2 \:\le \:0 $

In this case, the inequality would be true if $\displaystyle x \le 1$ and would essentially result in the domain restriction given in the problem.

When I take the derivative I get $\displaystyle \frac{x+1}{x-1}$. I must go to class now, but will post my work this afternoon if nobody else gets to it first - I'll check my work too (I could be wrong at this point).